2017
DOI: 10.1175/mwr-d-17-0068.1
|View full text |Cite
|
Sign up to set email alerts
|

GSI-Based, Continuously Cycled, Dual-Resolution Hybrid Ensemble–Variational Data Assimilation System for HWRF: System Description and Experiments with Edouard (2014)

Abstract: A Gridpoint Statistical Interpolation analysis system (GSI)-based, continuously cycled, dual-resolution hybrid ensemble Kalman filter–variational (EnKF-Var) data assimilation (DA) system is developed for the Hurricane Weather Research and Forecasting (HWRF) Model. In this system, a directed moving nest strategy is developed to solve the issue of nonoverlapped domains for cycled ensemble DA. Additionally, both dual-resolution and four-dimensional ensemble–variational (4DEnVar) capabilities are implemented. Vort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(76 citation statements)
references
References 63 publications
2
74
0
Order By: Relevance
“…It is found that hybrid DA techniques perform better than the nonhybrid 4DVAR method. Recently, Hamill, Whitaker, Kleist, et al (), Kutty et al (), Lu et al (, ), Schwartz et al (), and Wang () used hybrid DA techniques to study TC and found that the track and intensity prediction of TC initialized with hybrid DA was significantly better than the track forecast generated using only variational method. The result from the present study also matches well with these studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is found that hybrid DA techniques perform better than the nonhybrid 4DVAR method. Recently, Hamill, Whitaker, Kleist, et al (), Kutty et al (), Lu et al (, ), Schwartz et al (), and Wang () used hybrid DA techniques to study TC and found that the track and intensity prediction of TC initialized with hybrid DA was significantly better than the track forecast generated using only variational method. The result from the present study also matches well with these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Although these studies (Lu et al, . and Lu et al, ) show the positive impact of the flow‐dependent BEC estimated from different hybrid DA techniques on TC analysis and forecast compared to static BEC estimated from nonhybrid DA, there are limited studies over North Indian Ocean (NIO).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) 201111 Nanmadol 2011-08-24_06:00:00-2011-08-27_06:00:00 (2) 201117 Nesat 2011-09-25_06:00:00-2011-09-28_06:00:00 3201120 Banyan 2011-10-10_06:00:00-2011-10-13_06:00:00 (4) 201208 Vicente 2012-07-20_06:00:00-2012-07-23_06:00:00 (5) 201209 Saola 2012-07-29_06:00:00-2012-08-01_06:00:00 (6) 201213 Kai-tak 2012-08-14_06:00:00-2012-08-17_06:00:00 7201307 Soulik 2013-07-08_06:00:00-2013-07-11_06:00:00 (8) 201311 Utor 2013-08-10_06:00:00-2013-08-13_06:00:00 (9) 201319 Usagi 2013-09-17_06:00:00-2013-09-20_06:00:00 (10) 201409 Rammasun 2014-07-14_06:00:00-2014-07-17_06:00:00 (11) 201410 Matmo 2014-07-19_06:00:00-2014-07-22_06:00:00 (12) 201415 Kalmaegi 2014-09-12_06:00:00-2014-09-15_06:00:00 (13) 201510 Linfa 2015-07-05_06:00:00-2015-07-08_06:00:00 (14) 201513 Soudelor 2015-08-02_06:00:00-2015-08-05_06:00:00 (15) 201522 Mujigae 2015-10-01_06:00:00-2015-10-04_06:00:00 * The coordinated universal time was used in this study.…”
Section: Number Typhoon Cases Simulation Periodsmentioning
confidence: 99%
“…Several typhoon initialization methods exist to eliminate the uncertainty of the initial values, such as building a bogus vortex method [2][3][4][5], bogus data assimilation method [6][7][8][9][10], and a dynamical initialization method [11][12][13]. The uncertainty of the models' physical representation is another important source of simulation error, and many studies have focused on improvements to the model's physical processes for better simulation of tropical cyclones.…”
Section: Introductionmentioning
confidence: 99%